2009
DOI: 10.1007/s10295-009-0595-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of polygalacturonase enzyme activity and biomass production by Aspergillus sojae ATCC 20235

Abstract: Aspergillus sojae, which is used in the making of koji, a characteristic Japanese food, is a potential candidate for the production of polygalacturonase (PG) enzyme, which of a major industrial significance. In this study, fermentation data of an A. sojae system were modeled by multiple linear regression (MLR) and artificial neural network (ANN) approaches to estimate PG activity and biomass. Nutrient concentrations, agitation speed, inoculum ratio and final pH of the fermentation medium were used as the input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(19 reference statements)
0
10
1
Order By: Relevance
“…The number of hidden neurons is one of the most important parameters of ANN modeling. A high number of neurons performs adequately for training data but may fail for testing data (over-fitting), while having too few hidden neurons may result in unsatisfactory convergence (under-fitting) (Tokatli et al 2009). In this study, the number of neurons in the hidden layer was chosen by trial and error method, by varying the neurons from 3 to 12.…”
Section: Predictive Modeling Of Pg Activity Using Ann Effect Of Archimentioning
confidence: 99%
See 2 more Smart Citations
“…The number of hidden neurons is one of the most important parameters of ANN modeling. A high number of neurons performs adequately for training data but may fail for testing data (over-fitting), while having too few hidden neurons may result in unsatisfactory convergence (under-fitting) (Tokatli et al 2009). In this study, the number of neurons in the hidden layer was chosen by trial and error method, by varying the neurons from 3 to 12.…”
Section: Predictive Modeling Of Pg Activity Using Ann Effect Of Archimentioning
confidence: 99%
“…These results indicated that the prediction accuracy of ANN was better than the RSM model for our enzyme production process. Tokatli et al (2009) performed different ANN topologies to predict polygalacturonase (PG) activity as well with a 5-2-1 network topology (R 2 =0.84).…”
Section: Predictive Modeling Of Pg Activity Using Ann Effect Of Archimentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maintain viability, the fungus-grown plates were maintained at 4°C and subcultured monthly. Stock spore cultures were prepared using 20% glycerol and stored at -80°C (Tokatli et al 2009). Molasses agar slants were utilized to obtain the spore suspensions for inoculation.…”
Section: Microorganism and Inoculum Preparationmentioning
confidence: 99%
“…The first study using wild type of A. sojae 20235 resulted in 13.5 U/mL PG activity in SmF fermentation without microparticle (Tari et al 2007). Then, the maximum PG activity was enhanced to 20.1 U/mL using the same strain and medium (Tokatli et al 2009). Accordingly, the main objective of this study was not only to improve the fungal morphology of A. sojae by the addition of Al 2 O 3 into the fermentation media but also to increase the PG activity in microparticle-enhanced shake flask fermentation.…”
Section: Introductionmentioning
confidence: 99%